Bulut Bilişim ve Sağlık Bakımı. - TURAN, NURAY; KAYA, HATİCE (Journal of Education & Research in Nursing / Hemşirelikte Eğitim ve Araştırma Dergisi, 2017)
Nowadays, the increasing cost of health services requires healthcare institutions to adopt and use health information systems. Health information systems allow' healthcare institutions to organize their processes and offer more efficient services in a cost-effective way. Cloud computing, one of the most recent technological developments, makes it possible for healthcare institutions that offer health information services to create a powerful online data storage infrastructure. Despites the benefits, this new technology comes with various risks that may cause significant losses. This article aims to determine the impacts of cloud computing on healthcare systems and make recommendations for healthcare workers to develop awareness in cloud computing.